Prescription Patterns of Antituberculosis Drugs in Treatment of Tuberculosis at a Tertiary Care Hospital in Andgra Pradesh, a Cross-Sectional Study - Krishnakanth K; Chakrapani Cheekavolu; Poojala Kumar; Ravi Shankar K; Jagadeesh A (Pharmacology and Clinical Pharmacy Research)
The success of tuberculosis treatment is based upon the prescription pattern following Revised National Tuberculosis Control Program/National Tuberculosis Elimination Program/World Health Organization guidelines, reflecting the burden of the disease which is increasing yearly. This implicates the variations in prescriptions advised in the treatment of tuberculosis. The present study was aimed to evaluate the prescription patterns of tuberculosis treatment in a tertiary hospital at Andhra Pradesh, India. Ninety-two patients were included in the study after obtaining ethical approval and informed consent. The prescription patterns were evaluated and compared to the standard guidelines. The mean age of the patients was 38.72 and showed male preponderance. Six regimens were used during the treatment. The patients showed good recovery which concludes that following the standard prescription pattern provides a good success rate in the treatment of tuberculosis.